Application of micro-Raman spectroscopy for conservation projects in art and archaeology with a case study on Cappadocia rock-hewn wall paintings - Baraldi, Pietro; Baraldi, Cecilia; Pelosi, Claudia (Archeomatica, 2019)
This paper aims at reporting an overview of the principles and applications of micro-Raman spectroscopy in cultural heritage. Micro-Raman was used for characterizing painting pigments, inorganic binders, degradation materials in artworks with different goals: to know the materials and so the execution technique, to investigate the state of preservation, to establish the authenticity of the artefacts. The micro-Raman analyses were often performed on the occasion of conservative projects and they were able to supply valid and useful information to the conservators during their work. As a case study, the project on the investigation of rock-hewn wall paintings in Cappadocia (Turkey) will be shortly presented as an exemplification of application of Raman techniques for the knowledge of the constituent materials, for supporting the conservation work and for detecting degradation products. The analysis was performed in the Interdepartmental instrument Center of Modena and Reggio Emilia University by a benchtop system equipped with a microscope allowing for studying in non-destructive way different kinds of samples: powders, cross and thin sections, pre-treated samples.